2019
DOI: 10.1111/hdi.12793
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic exercise with blood flow restriction: Something to add to hemodialysis adequacy? Findings from a crossover study

Abstract: Introduction: Hemodialysis (HD) increases the lifespan of chronic kidney disease (CKD) patients. However, HD is only partially effective in replacing renal function. The aim of this study is to compare HD adequacy between sessions with intradialytic exercise with or without blood flow restriction (BFR) with sessions without exercise.Methods: A crossover study including 22 adult CKD patients on HD. The patients were assigned to BFR (n = 11) or exercise alone group (n = 11). Each patient was submitted to four HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although BFRT in chronic kidney disease (CKD) is a promising strategy to improve physical functioning and medical management of the condition, there exist some potential concerns regarding the widespread application of BFRT in Stage III/IV CKD patients. However, BFRT in end-stage renal disease, stage two CKD patients, hypertensive patients in stage II CKD, and patients on hemodialysis (Cardoso et al, 2020;Dias et al, 2020;Correa et al, 2021a,b) appear to display no adverse effects. Of note, all included CKD studies present stringent exclusion criteria (e.g., cardiovascular events in the last 3 months, acute infection, neoplastic process, pregnancy, inadequate blood pressure control displayed by SBP above 180 mmHg and/or DBP above 105 mmHg, heart rate above 120 bpm during hemodialysis, decompensated patients, diabetes mellitus, symptomatic heart failure; history of nephrolithiasis or coagulation, human immunodeficiency virus infection, surgery within the past 3 months, drug or alcohol abuse, pre-exercise BP above 160/100 mmHg, previous diagnosis of coronary artery disease, and admission to an intensive care unit).…”
Section: Chronic Kidney Disease and Blood Flow Restriction Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BFRT in chronic kidney disease (CKD) is a promising strategy to improve physical functioning and medical management of the condition, there exist some potential concerns regarding the widespread application of BFRT in Stage III/IV CKD patients. However, BFRT in end-stage renal disease, stage two CKD patients, hypertensive patients in stage II CKD, and patients on hemodialysis (Cardoso et al, 2020;Dias et al, 2020;Correa et al, 2021a,b) appear to display no adverse effects. Of note, all included CKD studies present stringent exclusion criteria (e.g., cardiovascular events in the last 3 months, acute infection, neoplastic process, pregnancy, inadequate blood pressure control displayed by SBP above 180 mmHg and/or DBP above 105 mmHg, heart rate above 120 bpm during hemodialysis, decompensated patients, diabetes mellitus, symptomatic heart failure; history of nephrolithiasis or coagulation, human immunodeficiency virus infection, surgery within the past 3 months, drug or alcohol abuse, pre-exercise BP above 160/100 mmHg, previous diagnosis of coronary artery disease, and admission to an intensive care unit).…”
Section: Chronic Kidney Disease and Blood Flow Restriction Trainingmentioning
confidence: 99%
“…BFR (at 50% of AOP) was applied during cycling exercise for 20 min within the first 2 h of hemodialysis with rate of perceived exertion of 12–13 (RPE Borg scale). Also, BFRT was shown effective as exercise alone in improving hemodialysis adequacy (e.g., how well blood is being cleansed), displaying a positive result in single-pool Kt/V-urea, equilibrated Kt/V-urea, urea reduction ratio, and urea rebound ( Dias et al, 2020 ).…”
Section: Chronic Kidney Disease and Blood Flow Restriction Trainingmentioning
confidence: 99%
“…Another strong concern when using BFR during intradialytic exercise is that it does not impact hemodialysis treatment ( Clarkson et al, 2020 ). Dias et al (2020) demonstrated that exercise training with BFR was effective as exercise alone in improving hemodialysis adequacy (e.g., how well blood is being cleansed), displaying a positive result in single-pool Kt/V-urea, equilibrated Kt/V-urea, urea reduction ratio, and urea rebound. Also, during intradialytic BFR training, the acute effect on dialysis adequacy and ultrafiltration rates were not different from the same patient’s usual care hemodialysis sessions ( Clarkson et al, 2020 ).…”
Section: Effects Of Bfr Exercise On Cardiovascular Outcomes and Renal...mentioning
confidence: 99%
“…Furthermore, four studies with BFR and CKD stated no adverse events from training in conventional exercise or with BFR ( Barbosa et al, 2018 ; Cardoso et al, 2020 ; Corrêa et al, 2021a ; Dias et al, 2020 ), while three did not specifically report adverse events ( Corrêa et al, 2021b ; de Deus et al, 2021 ; Deus et al, 2022 ). Thus, BFR exercise appears to be a potentially viable option for the kidney health professional to incorporate in a resistance or aerobic training exercise program.…”
Section: Bfr Exercise and Safety Concernsmentioning
confidence: 99%
“…While an in-depth discussion of the potential role of intradialytic exercise in this context is beyond the scope of the present review, the association of physical activity should probably be proposed on a similar scale, from rehabilitation exercises for fitter individuals to mild exercise during dialysis for those who are more fragile and have less support at home and to passive exercise for the patients who are in poor clinical condition [149][150][151][152][153][154][155][156].…”
Section: Are We Doing All We Can? the Role Of Intradialytic Exercisementioning
confidence: 99%